Protesting Children - Kowzan, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The purpose of this article is to describe the components of normalization of children's public dissent. We look specifically at the situation of their participation in an effective protest against a closure of an educational institution. Looking at the actual behavior of children in relation to power, we begin by showing the legal framework that legitimizes the participation of children in politics. Then we point to a number of historical examples of the collective participation of children in attempting to make a social change. With the criticism and debates of democracy and pedagogy theorists, these cases set a boundary for the possibility of a protest that involves children. The analysis of the case of children protesting in Gdańsk was conducted on the basis of video materials and took into account the adults? efforts to regulate the course of events. As a result, we learn that the protesting children may be framed into an emancipatory but objectifying narrative. What is more, their personal participation in the protest and their voice have the power to de-legitimise public dialogue.